ANALISIS DESAIN DAN PERHITUNGAN LAMPU PENERANGAN JALAN BERBASIS KENYAMANAN DAN KEAMANAN - Wijaya, I Ketut; Mataram, I Made (Jurnal SPEKTRUM, 2020)
Street lighting is installed for the benefit of the community to help build a creative economy. Street lights in the government's effort to create creativity help the family economy. The method used is counting the number of lights used on the road with a distance of 1500 meters and giving road users a questionnaire of comfort and safety. Street lighting is analyzed in an egonomic way to achieve effective, comfortable, safe, healthy and efficient work. The results obtained are the light intensity of 12.799 Lux (fulfilling SNI-2008) and the comfort and safety of 11.067 and 10,300 likes after improving conditions.